Blood Description, Parasite Investation and Survival Rate Of Carp (Cyprinus carpio) Which Is Exposed By Spore Protein Myxobolus koi On Rearing Pond as Immunostimulan Material - Laode Abdul Syafar (Universitas Airlangga, 2017)
ABSTRACTThis research is an experimental research to determine the effect of spore protein Myxobolus koi on grass carp (Cyprinus carpio) in rearing pond. The sample used is grass carp (Cyprinus carpio) 90 fish (10-15 cm). Spore protein used in this research is Myxobolus koi spore protein, that has been found by predecessor researchers and has been tested in laboratory as immunostimulan. The exposure was done orally, mixed in the feed, with a dose of 2 μg / gram dose of protein, feeded 1 time before being reared for 30 days. Parameters measured were: (1) leucocytes description (differentiated leucocytes of carp, (2) Parasitic infestation in carp and (3) Survival Rate / SR of carp were reared on pond for 30 days. The collected data is analyzed descriptively.The results showed that there was alteration of leukocytes description (differential leukocytes) in carp (Cyprinus carpio) as an indicator of the immune response. A leukocyte differential examination showed that exposure to the Myxobolus koi spore protein, The highest total lymphocytes occurred in carp exposed to Myxobolus koi spores protein and reared from pond in Mojokerto, were 77.6%, Monocytes of 16.3%, Heterophyll 14.4%, Eosinophils 7.6% and Basofil 0.4%. The highest infestation of Myxobolus koi occurred in fish that was not exposed to spore protein was 53.33% after 30 days of reared at pond, while parasitic infestation in fish exposed to spore protein was only 16.66%. Survival rate of carp indicated that the highest occurred in carp that exposed with spore protein and reared from pond in Mojokerto, equal to 90%.Myxobolus koi spore protein exposure given orally can makes alteration of leukocytes description (differential leukocytes), Decreased parasite infestation and increased survival of carp fish reared for 30 days, with the result that Myxobolus koi spore protein can be developed as an immunostimulant material.Keyword: Myxobolus koi, Cyprinus carpio, spore protein, immunostimulant, infestation